Improved limit on the directly measured antiproton lifetime. (31st August 2017) - Sellner, S; Besirli, M; Bohman, M; Borchert, M J; Harrington, J; Higuchi, T; Mooser, A; Nagahama, H; Schneider, G; Smorra, C; Tanaka, T; Blaum, K; et al.
Abstract: Continuous monitoring of a cloud of antiprotons stored in a Penning trap for 405 days enables us to set an improved limit on the directly measured antiproton lifetime. From our measurements we extract a storage time of 3.15 × 10 8 equivalent antiproton-seconds, resulting in a lower lifetime limit of τ p ̄ > 10.2 a with a confidence level of 68 % . This result improves the limit on charge-parity-time violation in antiproton decays based on direct observation by a factor of 7.